FUNGSI KEPEMIMPINAN DALAM PENINGKATAN KINERJA APARATUR SIPIL NEGARA DI BAGIAN HUMAS DAN PROTOKOL SEKRETARIAT KABUPATEN KUTAI TIMUR - . Rosma (Jurnal Administrative Reform, 2017)
This article aim to describe and analyze the leadership function in improving the performance of Civil state Apparatus in Public Relations Division and Secretariat Protocol of East Kutai Regency. The type of research is descriptive qualitative. Based on the results of the research indicates that the three roles of leadership are interpersonal roles, roles that are informational, and the role of decision-making in general has been done well by the leadership of Public Relations Division and Secretariat Protocol of East Kutai Regency. This is incicated from some programs and activities that has been done and the achievements achieved by employees in carrying out their duties and functions within the institution, so this also effect the improvement of the overall performance of the institution.Keyword : Leadership, Achievement